(1486) The trim - Loss reduction problem in industry مشكلة تقليل الفاقد في الصناعة - Youssef, Mohammed Yehia (The Institute of National Planning, 2018)
The process of‘ finding a best way is called , "optimisation‘.'l-.lost industrial projects involve the optimization ~ of a system, such as minimizing production costs, or minimizing . the cost of achieving certain technical properties for some ' engineering entity or operation. On the other hand, optimization may be maximizing profits or capacity of a flow of goods or information through a network, ...etc.